Aktivitas Antimikroba Hasil Fraksinasi Kortex Kayu Jawa (Lannea coromandelica (Houtt.) Merr.) - Isriany Ismail; Andi Armisman Edy Paturusi; Ilham Aridani (Biogenesis: Jurnal Ilmiah Biologi, 2016)
Kayu Jawa (Lannea cormendalica (Houtt.) Merr.) is native Indonesia plant, which became a typical plant for the treatment of wounds, dysentery, and other infectious diseases in some regions in Indonesia. An effort to explore of active compounds in medicinal plants in Indonesia, had tested the antimicrobial activity of the fraction Kayu Jawa cortex (Lannea coromandelica (Houtt.) Merr). This study aims to determine the polarity of compounds which can provide the best inhibitory activity against Bacillus subtilis, Escherichia coli, Pseudomonas aeruginosa, Salmonella thypi, Staphylococcus aureus, Staphylococcus epidermidis, Streptococcus mutans, Vibrio sp. and Candida albicans. Extraction of Kayu Jawa cortex done by maceration method with solvent n-hexane and methanol. Antimicrobial activity for total extracts was tested with TLC-Autobiographical and fractions of extract with best antimicrobial activity were tested by agar diffusion method. Fractionation conducted with Vacum-Liquid Chromatography (KCV) method with conditioned eluent from a solvent mixture of ethyl acetate:methanol and n-hexane:ethyl acetate. Determination of the class of active compounds done using a spray reagent.The results showed that the methanol extract and n-hexane extract inhibited the growth of bacteria Escherichia coli, Pseudomonas aeruginosa and Salmonella thypi. The fraction I of methanol extract at Rf 0.64 and fraction I extract n-hexane at Rf 0.02 showed antibacterial effectiveness for Escherichia coli, Salmonella thypi and showed strong inhibition at concentrations 500-750 ppm against Pseudomonas aeruginosa. The chemical components of the Kayu Jawa cortex (Lannea coromandelica (Houtt.) Merr.), which acts as an antimicrobial included in the class of flavonoids.